Evaluation of hospital admissions in the first 6 months after the COVID-19 discharge - Koç, Miraç; Önen, Özgür; Üzer, Begüm; Çalışır, Büşra; Kukul Güven, Fatma Mutlu (MediHealth Academy, 2023)
Aims: Although COVID-19 disease has many effects on patients after recovery, it is not known whether these effects are part of the recovery process or trigger other diseases. This study has aimed to investigate whether ferritin, which is used as an acute phase reactant to determine the severity and prognosis of the disease, has a role in determining the symptoms that occur after the disease. Methods: The study was conducted with 300 patients who were hospitalized with PCR positive and lung involvement. Patients' hospital admissions and initial ferritin levels were recorded within 6 months of discharge. It was examined whether there was a relationship between ferritin levels and the re-admission reasons. Results: 177(59.0) people had no symptoms during the six-month period and 123(41.0) patients were admitted to the hospital due to various symptoms. 6(2.0) of the patients became ex within six months after discharge. The most common symptoms in patients were 28(9.3) shortness of breath, 22(7.3) myalgia, 15(5.0) chest pain, 10(3.3) headache and 10(3.3) palpitations, respectively. Ferritin levels were found to be high in those with no symptoms and low in those with symptoms. Conclusion: Determining the symptoms, re-admissions, mortality rates and predictors that will guide Covid -19 is very important for the recognition, treatment and follow-up of this disease after discharge. More studies are needed to make a prediction according to ferritin levels in the process after recovery from Covid-19.
Keywords: 3. Good health